36 / 5.000 The Ecuadorian food problem - Villacreses, Jose L. (Revista Universidad de Guayaquil, 1988)
The food problem in our country, as in all third world countries, has transcendental connotations for the future of humanity. We really admire the statistical data related to nutritional deficiency in our country, and it is surprising because Ecuador is considered a blessed territory. decided by nature to have fertile lands for agriculture and ichthyologically prodigal seas. Wrong tactics in policies to reactivate agriculture, erroneous provisions emanating from governments regarding the marketing of food products, lack of infrastructure facilities for the preservation of seafood, and in general lack of a global conjunctural scheme of The entire food problem has caused the productive gap and consequently the deficit in many areas.